What Is the Prevalence of Hip Abductor Pathology in Patients Undergoing Total Hip Arthroplasty? - David A. Brethouwer, DO; Matthew L. Brown, MD; Julie C. McCauley, MPH; William D. Bugbee, MD; Eric Y. Chang, MD; Alecio F. Lombardi, MD; Brian J. Rebolledo, MD (Arthroplasty Today)
Background: Total hip arthroplasty (THA) is generally considered a successful operation for patients with advanced hip arthritis. Hip abductor pathology can lead to diminished outcomes. The prevalence of hip abductor pathology in patients undergoing THA is not well described. Methods: Our institution’s arthroplasty registry was queried to identify patients undergoing THA who had preoperative magnetic resonance imaging (MRI) of the hip or pelvis. MRIs were reviewed for presence of abductor (gluteus medius or gluteus minimus) tendon injury. Dysfunction of the abductor musculotendinous units was assessed by grading fatty infiltration of the muscle bellies using the Goutallier/Fuchs classification. Results: A total of 1090 primary THAs were performed during the study period, and 118 (10.8%) patients had a preoperative MRI of the hip or pelvis ≤12 months prior to surgery. Among the 118 patients who had an MRI, abductor tendon tears were diagnosed in 33 patients (28.0%), and tendinosis was noted in 106 patients (89.8%). Conclusions: There is a high prevalence of hip abductor pathology in patients presenting for THA. Clinicians should evaluate patients for signs of abductor tendon pathology when presenting for consideration of THA. Careful examination and MRI may be helpful to further evaluate the status of the gluteus minimus and gluteus medius musculotendinous units.